Magneto hydrodynamic convection in a nanofluid saturated enclosure with porous fins: Joint effects of MHD, nanoparticles, and porous morphology. Issue 8 (9th January 2020) - Wang, Lei; Cai, Yang; Wang, Wei-Wei; Liu, Run-Zhe; Liu, Di; Zhao, Fu-Yun; Wang, Hanqing
Abstract : Purpose: This paper aims to numerically investigate the magnetohydrodynamic (MHD) convection heat transfer of nanofluid inside a differentially heated enclosure with various fin morphologies. Design/methodology/approach: The fluid flow within the cavity was governed by N-S equations while it within porous medium was solved by the non-Darcy model, called the Darcy–Forchheimer model based on representative element-averaging method. Empirical correlations from experimental data are used to evaluate the effective thermal conductivity and dynamic viscosity. Relevant governing parameters, including thermal Rayleigh number (10 5 -10 7 ), Hartmann number (0-50), Darcy number (10 −6 -10 −1 ), thermal conductivity ratio of porous matrix (1-10 3 ), nanoparticles volume fraction (0-0.04) and topology designs of porous fins, are sensitively varied to identify their effects and roles on the fluid flow and heat transfer. Particularly, heatlines are used to investigate the mechanism of heat transport. Findings: Numerical results demonstrate that the predictions of average Nusselt number are augmented by using more porous fins with high permeability, and this effect becomes opposite in tiny Darcy numbers. Particularly, for high Darcy and Rayleigh numbers, the shortest fins could achieve the best performance of heat transfer. In addition, the prediction of average Nusselt number reduces with an increase in Hartmann numbers. An optimal nanoparticles concentration also exists to maximize heat transfer enhancement. Finally, numerical correlations for the average Nusselt number were proposed as functions of these governing parameters. Practical implications: Present work could benefit the thermal design of electronic cooling and thermal carriers in nanofluid engineering. Social implications: Present work could benefit the thermal design of electronic cooling and thermal carriers in nanofluid engineering. In addition, optimum thermal removals could enhance the lifetime of electronics, therefore reducing the cost of energy and materials. Originality/value: To the best knowledge of authors, there are not any studies considering the synergetic effects of porous fins on MHD convection of nanofluids. Present work could benefit the thermal design of electronic cooling and thermal carriers in nanofluid engineering.